STUDI SISTEM PENGELOLAAN SAMPAH BERBASIS KOMUNITAS ADAT DI DESA ADAT SEMINYAK KECAMATAN KUTA KABUPATEN BADUNG - I. A. Trisna Eka Putri; N.K. Mardani; I. B.G. Pujaastawa (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science))
Study of community based waste management system at Desa Adat Seminyak- Kuta, Badung Regency, has done on June until October 2009. The aims of this study to know about : (1) characteristic and volume of waste at Desa Adat Seminyak; (2) community based waste management system at Desa Adat Seminyak; (3) role of the household and tourism in supporting industry on waste management system at Desa Adat Seminyak; (4) strategic for the suitable pattern of the waste management which can be applied at Desa Adat Seminyak. This study was conducted with direct observation at the TPST in Desa Adat Seminyak and also in the surrounding area of the Desa Adat Seminyak. The distribution of questionaire and conducting direct interview with some institutions that related on the service of waste management and library studies. Analyze data used is description analyze which supporting with Internal (IFAS) and External (EFAS) analyze to obtain grand strategy, SWOT analyze to alternative strategy of the waste management system at Desa Adat Seminyak. Result of this study showed that : (1) organic waste has highest percentage of waste Desa Adat Seminyak than another such as plastic, paper, textile, glass and box, with volume level 32,29 m3/day; (2) waste management system of adat community at Desa Adat Seminyak is conducting with the bottom up system to find a better solution on waste management, the role of participation of the adat community is conducting some processes : planning process, cooperate process, command and evalution process, and also advantage process; (3) role of the household on waste management system, more than 70% household participation at waste disposal, waste banisment, waste reuse, transfer system and payment of waste distribution. For 97,78% of the household less participation on waste regulations. Role of tourism supporting industry on the waste management was less optimal that 86,67% of tourism supporting industry not yet had waste handling which waste handling was done by desa adat; (4) grand strategy will be implemantation in waste management system at Desa Adat Seminyak is growth oriented strategy, and SWOT analized to find strategy alternative etc : (1) prosperity strategic of the waste management; (2) strategic to improving institutions and human resources; (3) strategic to prosperity on waste handling; (4) strategic to improving quality of waste management.